Optimalisasi Pengelolaan Beban Kerja Hakim Dan Implikasinya Terhadap Integritas Dan Kualitas Peradilan - Samiri, Muliani; Kasim, Muhammad Adil; Nonci, Nurjannah; Ahmad, Jamaluddin; Putra, Muhammad Alif Adimulia (PROGRAM STUDI MAGISTER HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO, 2025)
High workload is a major challenge for the Indonesian legal system. Judges face a high number and level of complexity of cases, which leads to a decline in the quality of decisions and the integrity of the judiciary. The purpose of this study is to analyze the impact of excessive workload on the quality of legal decisions, assess the relationship between workload and judicial integrity, and identify factors that trigger ethical violations. The method used in this study is a normative legal approach, analyzing secondary data from court decisions, annual reports of the Supreme Court, and relevant legal literature. The findings of this study indicate that high workloads lead to fatigue, high stress levels, and limited time for judges to thoroughly consider cases, which in turn trigger ethical violations, conflicts of interest, and inconsistent rulings. In conclusion, optimizing the workload by increasing the number of judges, improving case management, and strengthening the oversight system are some recommendations that need to be prioritized in the implementation of the judicial system.